Investigation on Effect of Egg Shell Powder on Mechanical Properties of GFRP Composites. (2018) - Hiremath, Pavan; Shettar, Manjunath; Shankar, M.C. Gowri; Mohan, N.S.
Abstract: The production and worldwide use of chicken eggs on an industrial or domestic level leads to a considerable quantity of shell residue, which is considered as a waste or is used as a complement in agriculture. Use of waste materials in polymer matrix composites is on the rise mainly due to environmental and economic apprehensions. The present work is focused on to analyse the influence of egg shell powder as filler materials on the mechanical behaviour of glass fibre, reinforced resin matrix. Different types of composites are fabricated using 5 wt% egg shell powder and 10 wt% egg shell powder with 50 wt% fibre, rest matrix material. The composites are manufactured by hand-layup process. Specimens cut and tested according to ASTM standards. The mechanical and physical properties are studied. The results are compared for different percentage of filler material.